Measuring Recovery in Elite Rugby Players: The Brief Assessment of Mood, Endocrine Changes, and Power - Liam Kilduff (Research Quarterly for Exercise and Sport, 2015)
Purpose: There is demand in applied sport settings to measure recovery briefly and accurately. Research indicates mood disturbance as the strongest psychological predictor of mental and physical recovery. The Brief Assessment of Mood (BAM) is a shortened version of the Profile of Mood States that can be completed in less than 30 s. The purpose of this study was to examine the BAM as a quick measure of mood in relation to recovery status in elite rugby players alongside established physiological markers of recovery. Method: Using elite rugby union players (N = 12), this study examined the utility of BAM as an indicator of mental and physical recovery in elite athletes by exploring pattern change in mood disturbance, energy index, power output, cortisol, and testosterone 36 hr before and 12 hr, 36 hr, and 60 hr after a competitive rugby match. Results: Repeated-measures multivariate analysis of variance indicated significant changes in all variables across the 4 time points (p < .05, η2 range = .20–.48), concurrent with previous study findings. Although visual inspection of the graphs indicated that the pattern of change for mood disturbance and energy index mapped changes in all physiological variables, only a low correlation was observed for power output (r = − .34). Conclusions: Although BAM scores changed significantly over time in accordance with the hypotheses, further testing is required to confirm the utility of the BAM as a measure of recovery. The results indicate that the BAM could be used as 1 indicator of recovery status alongside other measures.